The complete mitogenome of the Arctic moss Aulacomnium turgidum (Wahlenb.) Schwaegr - Pilsung Kang; Sung Mi Cho; Jungeun Lee; Joung Han Yim; Jun Hyuck Lee; Hyoungseok Lee (Mitochondrial DNA. Part B. Resources, 2019)
The Arctic moss Aulacomnium turgidum (Wahlenb.) Schwaegr. is distributed widely above the Arctic Circle and can regenerate successfully after 400 years of ice entombment. Here, we report the complete mitogenome sequence of A. turgidum (103,937 bp). The genome contains 3 ribosomal RNAs, 24 transfer RNAs, and 40 protein-encoding genes. In a phylogenetic tree generated using the combined amino acid sequences of 32 mitochondrial genes from A. turgidum, 25 Bryophyta, and three Marchantiophyta, the phylogenetic position of A. turgidum (Rhizogoniales) is close to that of the Hypnales and Ptychomniales, forming a monophyletic clade with perfect supporting values.